(untitled) (Praxis Educativa, 2026)
This article analyzes the configurations of three religion class programs in the Chilean school system, focusing on the approaches and justifications that support them. The three programs are: Catholicism, Evangelicalism, and the Baha’i Faith. Based on a content analysis, complemented by interviews with program designers and teachers, it emerged that the Catholic religion program bases its content on divine revelation interpreted by a tradition,which challenges the reader. The Evangelical religion program is based on the Bible, which reveals a perennial truth. The Baha’i Faith program posits that each religion contributes aspects of divine revelation; its content showcases components of various religions to advance the unity of humanity. At the end of the article, some implications of these results for the legitimacy of religion classes in public schools are discussed.